NEUROPATI PERIFER PADA PENYANDANG TALASEMIA DI POLIKLINIK HEMATO-ONKOLOGI RSUP DR. HASAN SADIKIN BANDUNG - Uni Gamayani; Fanny Adhy Putri; Nushrotul Lailiyya; Pandji Irani Fianza; Ramdan Panigoro (PERDOSNI, 2019)
PERIPHERAL NEUROPATHY IN THALASSEMIA PATIENTS AT HAEMATO-ONCOLOGY CLINIC HASAN SADIKIN GENERAL HOSPITAL BANDUNGABSTRACTIntroduction: Thalassemia is an inherited blood disorder with high prevalence that can lead to various neurological complications such as peripheral neuropathy. Peripheral neuropathy in thalassemia patients is commonly subclinical. Chronic hypoxia due to anemia and iron deposition are thought to be the risk factors for neuropathy in thalassemia. Nerve Conduction Study (NCS) is the gold standard in diagnosing peripheral neuropathy.Aims: To identify peripheral neuropathy among thalassemia patients in Hemato-oncology Clinic at Hasan Sadikin General Hospital, Bandung.Method: This was a cross sectional, observational descriptive study conducted on thalassemia patients who regularly underwent blood transfusion in Haemato-oncology Clinic at Hasan Sadikin General Hospital, Bandung. The study was held from November 2017 until March 2018. All subjects who met inclusion criteria and did not meet any exclusion criteria were assessed with neurological examination, Toronto clinical score and NCS.Results: Forty subjects with mean age 21.8±6.4 years old, 57.5% were female. The mean hemoglobin level was 7.3±0.7g/dL and mean ferritin serum level was 5,032±3,423μg/L. The median Toronto clinical s c o r e was 4 (0-7) with normal, mild neuropathy, and moderate neuropathy in 55%, 42.5%, and 2.5% subjects respectively. Ninety percent patients had abnormal NCS examination with axonal degeneration found in 57.5% subjects and polyneuropathy in 82.5% subjects.Discussion: Peripheral neuropathy were found in most adult thalassemia patients. Although, NCS examination is important to established definitive diagnosis and considered to be performed in thalassemia patients to diagnose peripheral neuropathy.Keywords: NCS, peripheral neuropathy, thalassemia, Toronto clinical scoreABSTRAKPendahuluan: Talasemia adalah penyakit kelainan darah herediter dengan prevalensi tinggi dan menimbulkan komplikasi neurologis berupa neuropati perifer. Neuropati perifer pada penyandang talasemia seringkali bersifat subklinis. Hipoksia jaringan akibat anemia kronis dan deposisi besi karena transfusi dicurigai sebagai faktor risiko terjadinya neuropati perifer pada talasemia. Standar baku diagnosis neuropati perifer adalah dengan pemeriksaan Kecepatan Hantar Saraf (KHS).Tujuan: Untuk mengetahui adanya neuropati perifer pada penyandang talasemia di Poliklinik Hemato-OnkologiMedik RSUP Dr. Hasan Sadikin, Bandung.Metode: Penelitian ini bersifat deskriptif observasional, dengan rancangan potong lintang, dilakukan pada subjek penyandang talasemia yang rutin menjalani transfusi di Poliklinik Hemato-Onkologi Medik RSUP Dr. Hasan Sadikin, Bandung. Penelitian dilakukan sejak November 2017 sampai Maret 2018. Seluruh subjek yang memenuhi kriteria inklusi dan tidak memiliki kriteria eksklusi dilakukan pemeriksaan neurologis, skor klinis Toronto dan KHS.Hasil: Sebanyak 40 subjek berusia rerata 21,8±6,4 tahun, 57,5% perempuan. Rerata kadar hemoglobin 7,3±0,7g/ dL dan rerata kadar feritin 5,032±3,423μg/L. Skor klinis neuropati Toronto didapatkan median 4 (0-7) dengan interpretasi tidak ada neuropati, neuropati ringan dan neuropati sedang berturut-turut pada 55%, 42,5%, dan 2,5% subjek. Sebanyak 90% subjek memiliki gambaran KHS abnormal, polineuropati didapatkan pada 82,5% subjek dan gambaran degenerasi aksonal pada 57,5% subjek.Diskusi: Neuropati perifer terjadi pada sebagian besar penyandang talasemia dewasa. Pemeriksaan KHS diperlukan untuk diagnosis pasti dan dipertimbangkan untuk dilakukan pada penyandang talasemia.Kata kunci: KHS, neuropati perifer, skor klinis Toronto, talasemia